Pengaruh Komunikasi Interpersonal Guru dengan Siswa Terhadap Motivasi Belajar Siswa di SMP Muhammadiyah 7 Wuluhan - Ilmiyah, Ilmin; Sofi, Sofyan; Huda, Hairul (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Student motivation is a crucial factor in enhancing the quality of the learning process and outcomes in educational institutions. One of the factors influencing motivation is the interpersonal communication between teachers and students. This study aims to examine the influence of teachers' interpersonal communication on students' motivation to learn at SMP Muhammadiyah 7 Wuluhan. The research adopts a quantitative approach with simple linear regression to predict motivation based on interpersonal communication. Data were collected through questionnaires distributed to students and analyzed using statistical methods. The results indicate a positive and significant effect of teachers' interpersonal communication on students' motivation to learn. These findings highlight the importance of effective communication in creating a conducive learning environment and increasing student motivation. This research is expected to provide recommendations for educational stakeholders to improve teachers' interpersonal communication competencies to enhance students' motivation.